JURIDICAL AND ADMINISTRATIVE REVIEW OF THE STORAGE OF KPK CONFISCATED ASSETS IN THE CIREBON CITY RUPBASAN - Muhammad Farhan Ghaisan; Wahyu Maulana Agung; Paksi Anggana Firdaus; Muhammad Irfandi; Adam Nugraha (Ann Publisher, 2025)
Abstract Background. The State Confiscated Goods Storage House (Rupbasan) is vital in Indonesia's criminal justice system. Its primary function is to store, manage, and maintain confiscated goods and state spoils to remain in good condition until the legal process is completed. Aims. This study discusses the critical role of the State Confiscated Goods Storage House (Rupbasan) in the criminal law system in Indonesia, by highlighting the case of storing assets belonging to Sunjaya Purwadisastra, the former Regent of Cirebon, which was confiscated by the Corruption Eradication Commission (KPK). Result. The study found inconsistencies between the rule of law and its implementation in the field, caused by limited funds, facilities, and weak coordination between institutions. The national budget efficiency policy also affects the operations of the Rupbasan, so there is a discourse on merging the Rupbasan's functions into the Attorney General's Office. Methods. This research uses a normative qualitative approach to analyze the legal and administrative aspects of confiscated asset management. Conclusion. The results show the need for regulatory reform, system modernization, institutional capacity building, and budget policy evaluation. Implication. This study suggests that the management of state assets is carried out in a transparent, accountable, and fair manner in order to maintain legal integrity and prevent state losses.